Activation of Quinolines by Cationic Chalcogen Bond Donors - Wonner, P.; Steinke, T.; Huber, S. M. (Synlett, 2019)
The application of already established as well as novel selenium- and sulfur-based cationic chalcogen bond donors in the catalytic activation of quinoline derivatives is presented. In the presence of selected catalysts, rate accelerations of up to 2300 compared to virtually inactive reference compounds are observed. The catalyst loading can be reduced to 1 mol% while still achieving nearly full conversion for electron-poor and electron-rich quinolines. Contrary to expectations, preorganized catalysts were less active than the more flexible variants.
Keywords: chalcogen bonding; Lewis acids; organocatalysis; noncovalent interactions; intermolecular interactions; chalcogens; reduction